Sortilin Fragments Deposit at Senile Plaques in Human Cerebrum - Hu, Xia; Hu, Zhao-Lan; Li, Zheng; Ruan, Chun-Sheng; Qiu, Wen-Ying; Pan, Aihua; Li, Chang-Qi; Cai, Yan; Shen, Lu; Chu, Yaping; Tang, Bei-Sha; Cai, Huaibin; et al. (Frontiers in Neuroanatomy, 2017)
Genetic variations in the vacuolar protein sorting 10 protein (Vps10p) family have been linked to Alzheimer’s disease (AD). Here we demonstrate deposition of fragments from the Vps10p protein sortilin at senile plaques (SPs) in aged and AD human cerebrum. Sortilin changes were characterized in postmortem brains with antibodies against the extracellular and intracellular C-terminal domains. The two antibodies exhibited identical labeling in normal human cerebrum, occurring in the somata and dendrites of cortical and hippocampal neurons. The C-terminal antibody also marked extracellular lesions in some aged and all AD cases, appearing as isolated fibrils, mini-plaques, dense-packing or circular mature-looking plaques. Sortilin and β-amyloid (Aβ) deposition were correlated overtly in a region/lamina- and case-dependent manner as analyzed in the temporal lobe structures, with co-localized immunofluorescence at individual SPs. However, sortilin deposition rarely occurred around the pia, vascular wall or areas with typical diffuse Aβ deposition, with the labeling not enhanced by section pretreatment with heating or formic acid. Levels of a major sortilin fragment 15 kDa, predicted to derive from the C-terminal region, were dramatically elevated in AD relative to control cortical lysates. Thus, sortilin fragments are a prominent constituent of the extracellularly deposited protein products at SPs in human cerebrum.